Accounting for managers : interpreting accounting information for decision-making - Collier, Paul M. (John Wiley & Sons Ltd., 2003)
Summary: Accounting for Managers explains how accounting information is used by non-financial managers. The book emphasises the interpretation, rather than the construction, of accounting information and encourages a critical, rather than unthinking acceptance, of the underlying assumptions behind accounting. It links theory with practical examples and case studies drawn from real life business situations in service, retail and manufacturing industries.